WARNA BERBICARA - Mr. Pujiyanto (DeKaVe, 2011)
Colors can not be kissed, heard, or touched, but can be seen. Color can only be seen with eyes and felt in the heart. Color is not a living thing and can not read but it can "talk". In this context, the color has flexible properties when applied to various objects and subjects. Colors and symbols have specific meanings in the social cultural society. Colors can "talk" soft and hard through the symbols and meanings in objects or subjects that apply.Keywords : color, application, trust, violence, political, institutional, product.